An In-Depth Comparative Analysis of Hemodynamic Alterations Under General and Spinal Anesthesia During Hernia Repair Procedures - AHMED JULAB, HIDER (Pain medicine, 2025)
Introduction: Ensuring patient safety remains the foremost concern for anesthesia and critical care teams when determining the most suitable anesthetic approach, whether in terms of techniques, drugs, strategies, or guidelines. Among the available options, spinal anesthesia is one of the most widely used and effective methods for patients undergoing hernia repair. Subjects and methods: This study involved a thorough and up-to-date assessment of patients undergoing herniotomy. A total of 100 patients were enrolled and divided equally into two groups: 50 received spinal anesthesia (SA) and 50 received general anesthesia (GA). Key parameters such as age, weight, pulse rate, and blood pressure changes were monitored. Patients aged between 20 and 90 years were allocated to the GA and SA groups for detailed preoperative, intraoperative, and postoperative follow-up. Results: Findings indicate that hemodynamic stability was greater with SA (approximately 56 %) compared to GA (around 40 %). Blood pressure levels were higher in GA (32 %) versus SA (24 %), while hypotension occurred in 28 % of GA cases and 20 % of SA cases. Heart rate stability was also better with SA (56 %) compared to GA (32 %). An increased heart rate was observed in 34 % of SA patients and 60 % of GA patients. Overall, SA showed more consistent effects, with a heart rate reduction of 10 % compared to an 8 % reduction in GA. Conclusions: Spinal anesthesia demonstrated superior outcomes compared to general anesthesia in maintaining stable blood pressure and ensuring minimal or normal heart rate fluctuations.